Strategi Media Relations Humas Dinas Pariwisata yang Berbasis Digital dalam Mempromosikan Kota Makassar - Nethanya Angel Tarantein; Tazkiyatunnisa Abd Karim; Egi Pramudiya; Akbar Abu Thalib (JISPENDIORA Jurnal Ilmu Sosial Pendidikan Dan Humaniora, 2025)
This study aims to analyze the digital-based media relations strategy implemented by the Public Relations Division of the Makassar City Tourism Office in promoting the city’s tourism potential. The research stems from the fact that Makassar’s high tourism potential has not been fully optimized through digital promotion, despite the wide reach and effectiveness offered by the digital era. This research employs a qualitative descriptive method, using in-depth interviews, observations, and documentation of the Tourism Office’s promotional activities. The findings reveal that digital platforms such as Instagram, TikTok, Facebook, the official website exploremakassar.com, and the Makassar Tourism mobile application serve as the main pillars of the promotional strategy. TikTok and Instagram have proven to be the most effective channels with the highest interaction rates, particularly among younger audiences. The promotion strategy focuses more on owned media to ensure cost efficiency and message control, although budget constraints limit collaboration with external media. Adaptation to changes in public behavior after the COVID-19 pandemic has also accelerated the shift from conventional promotion methods to interactive digital-based approaches. This study concludes that the implemented digital media relations strategy is relevant to modern communication trends, cost-efficient, yet still faces challenges in expanding promotional reach to national and international levels. It is recommended to expand collaboration with external media, enhance interactive content creativity, strengthen human resources capacity in digital marketing, and develop multilingual promotional content to broaden the target audience